The Impact of Extreme Weather Events on Mental Health in Africa: A Mixed-Methods Systematic Review - Deglon, Michaele (Department of Public Health and Family Medicine, 2023)
Introduction: The psychosocial impacts of extreme weather events are contributing to the burden of mental illness, exacerbated by pre-existing vulnerabilities. Despite an emerging global interest in this association, Africa remains poorly represented in the literature. Methods: A mixed-methods systematic review of peer-reviewed studies was conducted to determine the adverse mental health outcomes associated with extreme weather events in Africa (2008-2021). The review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: A total of 12 204 peer-reviewed articles were identified of which 12 were retained for analysis. These studies were all conducted in 8 countries in Sub-Saharan Africa. Adverse mental health outcomes were identified resulting from flood (n=4), drought (n=4), extreme heat (n=1), bushfire (n=1), and multiple events (n=2). Findings included pathological outcomes with predictable symptomatology including mood disorders; trauma- and stressor-related disorders; and suicide. Additionally, conditions indicating psychological distress which were below the pathological threshold including emotion regulation difficulties, disturbed sleep, alcohol use, stress, and anxiety. The quantitative evidence for the association between extreme weather events and mental health was limited primarily by a lack of longitudinal data, exposure gradient, and comparison to an unaffected group, as well as a failure to provide an objective exposure measure. The qualitative evidence for this association was complimentary but without sufficient clinical measurement these outcomes cannot be verified as psychological morbidities. In addition, this review provided insight into the mental health of vulnerable communities affected by extreme weather events including those living in poverty, farmers, pastoralists, women, and children. Conclusion: This review provided some preliminary evidence for the association between extreme weather events and adverse mental health outcomes for populations in Africa. The review also provides insight to vulnerable populations affected by extreme weather events. Future research with stronger designs and methodologies are recommended.